Case Report: Acute Necrotizing Encephalopathy Following COVID-19 Vaccine - Bensaidane, Mohamed Reda; Picher-Martel, Vincent; Émond, François; De Serres, Gaston; Dupré, Nicolas; Beauchemin, Philippe (Frontiers in Neurology, 2022)
Objectives Acute necrotizing encephalopathy (ANE) is a rare neurological disorder arising from a para- or post-infectious “cytokine storm. ”It has recently been reported in association with coronavirus disease 2019 (COVID-19) infection. Methods A 56-year-old male with a diagnosis of ANE 48 h following the first dose of ChAdOx1 nCoV-19 vaccination was investigated. Cytokine analyses on serum and cerebrospinal fluid (CSF) were performed. The patient was treated with high-dose corticosteroids and followed clinically and radiologically. Results Favorable clinical and radiological outcomes were noted. There was an upregulation in serum levels of CXCL5, CXCL1, Il-8, IL-15, CCL2, TGF-B, and EGF, and up-regulation in CSF levels of CXCL5, IL-2, IL-3, and IL-8. Discussion As COVID-19 infection has been previously reported as a possible rare cause of ANE, we speculate on an aberrant immune response mechanism that was brought about by the vaccine. To increase our understanding of the pathogenesis of ANE in the context of COVID-19 vaccination and to better define its clinical features and outcomes, clinicians and scientists should continue reporting convincing cases of such entities.